2011
DOI: 10.1159/000324175
|View full text |Cite
|
Sign up to set email alerts
|

Nutrigenomics, Vitamin D and Cancer Prevention

Abstract: Although there is growing epidemiological, preclinical and clinical evidence suggesting that low vitamin D intake, exposure and/or status is associated with an increased risk of various types of cancer, the optimum amount needed remains controversial. Furthermore, there is evidence that a U- or J-shaped response curve exist between 25(OH)D and certain cancers. Increasing information about the impact of genetic variation, especially polymorphisms that influence absorption, transport, metabolism and associated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 147 publications
(101 reference statements)
0
21
0
1
Order By: Relevance
“…In humans, vitamin D is obtained mainly through synthesis in skin by exposure to sunlight and, to a lesser extent, by directly ingestion in certain foods or supplements. Unfortified foods that contain vitamin D naturally are limited mainly to oily fish, liver, and egg yolks (23). Even with optimal nutrition, however, up to 90% of our daily vitamin D requirement is met through cutaneous production driven by exposure to sunlight (24).…”
Section: Vitamin Dmentioning
confidence: 99%
“…In humans, vitamin D is obtained mainly through synthesis in skin by exposure to sunlight and, to a lesser extent, by directly ingestion in certain foods or supplements. Unfortified foods that contain vitamin D naturally are limited mainly to oily fish, liver, and egg yolks (23). Even with optimal nutrition, however, up to 90% of our daily vitamin D requirement is met through cutaneous production driven by exposure to sunlight (24).…”
Section: Vitamin Dmentioning
confidence: 99%
“…Numerous studies have suggested that lower vitamin D level is a risk factor for human cancers, and vitamin D deficiency linked with the incidence and mortality of many types of cancers, including breast, colon, and prostate cancers [43,44].…”
Section: Vitamin D and Cancermentioning
confidence: 99%
“…VDR also played important role in anticancer effect. Some preliminary data suggested that VDR polymorphisms were more frequently associated with tumor genes which are Fok1, Bsm1, Taq1, Apa1, EcoRV, and Cdx2 [43][44][45].…”
Section: Vitamin D and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Upon ligand binding, VDR heterodimerize with RXR or RAR, and regulate the transcription of more than a hundred genes, involved not only in calcium and phosphate homeostasis but also in cell proliferation, differentiation, and apoptosis (Chung et al 2009). Accumulating results revealed the association between vitamin D deficiency and vitamin D-related genes with different cancer types, including breast, prostate, colorectal, oral, lung cancer, melanoma and acute myeloid leukemia (Feldman et al 2014;Davis and Milner 2011;Zeljic et al 2012, Puccetti et al 2002. In addition, the gene expression of VDR and CYP24A1 gene, coding for 24-hydroxylase, enzyme involved in the vitamin D catabolism, and CYP27B1, coding for 1α-hydroxylase, involved in anabolism, is mediated by epigenetic modifications (Hobaus et al 2013;Fetahu et al 2014).…”
Section: Essential Micronutrientsmentioning
confidence: 99%